Best Answer

2x + 3 is an expression that is already in simplest form; you cannot "solve" it.

Q: How do you solve 2x plus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x+3 = 7 2x = 7-3 2x = 4 x = 2

3x+4 = 2x-3 3x-2x = -3-4 x = -7

2x + 3 = 9 To solve Subtract '3' from both sides 2x = 6 Divide both sides by '2' x = 3 The Answer!!!!!

If we assume that it equals zero and you wish to solve for x, then the answer is:-x2 + 2x - 3 = 0x2 - 2x + 3 = 0x2 -2x + 1 = -2(x - 1)2 = -2x - 1 = ± √(-2)x = 1 ± i√2

2x + 2/3= 5/3 2x= 3/3 2x=1 x=1/2

Related questions

4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4

3

2x+3 = 7 2x = 7-3 2x = 4 x = 2

2x+3 = -11 2x = -11-3 2x = -14 x = -7

2x + 3 = x 2x + 3 - 3 = x - 3 2x = x - 3 2x - x = x - 3 - x x = -3

3x+4 = 2x-3 3x-2x = -3-4 x = -7

2x + 3 = 9 To solve Subtract '3' from both sides 2x = 6 Divide both sides by '2' x = 3 The Answer!!!!!

3x-2 = 2x+3 3x-2x = 3+2 x = 5

If we assume that it equals zero and you wish to solve for x, then the answer is:-x2 + 2x - 3 = 0x2 - 2x + 3 = 0x2 -2x + 1 = -2(x - 1)2 = -2x - 1 = ± √(-2)x = 1 ± i√2

2x + 2/3= 5/3 2x= 3/3 2x=1 x=1/2

Solve for x. 3x + 3 = x + 7 2x + 3 = 7 2x = 4 x = 2 Check it. 6 + 3 = 2 + 7 It checks.

3x + 2x = 5x